2000
DOI: 10.1080/009841000156574
|View full text |Cite
|
Sign up to set email alerts
|

SILICA-INDUCED NUCLEAR FACTOR- k B ACTIVATION: INVOLVEMENT OF REACTIVE OXYGEN SPECIES AND PROTEIN TYROSINE KINASE ACTIVATION

Abstract: Nuclear factor-kappaB (NF-kappaB) is a multiprotein complex that may regulate a variety of inflammatory cytokines involved in the initiation and progression of silicosis. The present study documents the ability of in vitro silica exposure to induce DNA-binding activity of NF-kappaB in a mouse peritoneal macrophage cell line (RAW264.7 cells) and investigates the role of reactive oxygen species (ROS) and/or protein tyrosine kinase in this activation. In vitro exposure of mouse macrophages to silica (100 microg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Silica-induced ROS generation results in up-regulation of NF-κB and production of proinflammatory cytokines ( Rojanasakul et al. , 1999 ; Kang et al. , 2000 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silica-induced ROS generation results in up-regulation of NF-κB and production of proinflammatory cytokines ( Rojanasakul et al. , 1999 ; Kang et al. , 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide is converted to hydrogen peroxide (H 2 O 2 ) by superoxide dismutase or by spontaneous dismutation, and H 2 O 2 is neutralized by peroxidases or catalase ( Kalyanaraman, 2013 ). An increase in cytoplasmic and mitochondrial reactive oxygen species (ROS) occurs upon silica exposure ( Kang et al. , 2000 ; Fazzi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that H 2 O 2 enhanced p65 NFκB DNA-binding and promoted p65 NFκB phosphorylation. This NFκB activation is followed by its translocation into the nucleus in macrophage and monocytic cell lines, and then induces M1 polarization (133). In parallel, it was shown that H 2 O 2 altered protein–protein interaction of p50–p50 NFκB, therefore reducing p50–p50 NFκB activation, supporting M1 activation (134).…”
Section: Targeting Tams With Rtmentioning
confidence: 99%
“…For instance, the NAC pretreatment of silica-exposed murine macrophage cell line 264.7 lowered the TNFα mRNA and protein levels and the mRNA levels of MIP-2, MIP-1α, MIP-1β, and MCP-1 [ 186 ]. Two other studies demonstrated that the silica exposure-induced overproduction of ROS is associated with the degradation of the NF-κB inhibitor IκB-α and activation of the NF-κB pathway because a pretreatment with NAC decreased a silica-induced accumulation of ROS and inhibited the suppression of IκB-α [ 179 ], or reduced the activation of NF-κB [ 187 ]. In alveolar macrophages isolated from silica-instilled rats [ 188 ] or exposed in vitro to silica, the silica-induced elevation in intracellular ROS was associated with a decrease in intracellular GSH and cysteine and a sustained presence of apoptotic alveolar macrophages.…”
Section: Nac In Chronic Respiratory Diseasesmentioning
confidence: 99%